Warm and humid environment induces gut microbiota dysbiosis and bacterial translocation leading to inflammatory state and promotes proliferation and biofilm formation of certain bacteria, potentially causing sticky stool - Yinrui Guo; Jianlang He; Shaojie Li; Shiqi Zou; Haiting Zhang; Xin Yang; Jian Wang (BMC Microbiology)
Abstract Background and aims of the study Fluctuations in environmental temperature and humidity significantly affect human physiology and disease manifestation. In the Lingnan region of China, high summer temperatures and humidity often cause symptoms like diminished appetite, sticky tongue coating, sticky stool, unsatisfactory defecation, lethargy, and joint heaviness. These are referred to as “Dampness Syndrome” in Traditional Chinese Medicine (TCM). Thick and greasy tongue fur and sticky feces are characteristic symptoms of “Dampness Syndrome” and serve as crucial diagnostic indicators in TCM for assessing health conditions. However, the specific mechanisms that lead to these symptoms, such as sticky feces and thick and greasy tongue fur, have not been fully elucidated. Understanding these external symptoms is essential, as they reflect internal health status. Warm, humid environments favor microorganism growth, potentially disrupting gut microbiota and bacterial translocation, which could induce an immune-inflammatory response. The primary objective of this study is to explore the potential significant role of immune response products in influencing the proliferation and biofilm formation of gut microbiota, which may subsequently lead to changes in fecal characteristics. Methods In this study, mice were exposed to a controlled warm and humid environment (25 ± 3 °C with 95% humidity) for 16 days to simulate conditions associated with “Dampness Syndrome.” After this period, Huoxiang Zhengqi Water, a traditional remedy, has been administrated for four days. On the one hand saliva and tongue coating samples were also taken from human subjects with “Dampness Syndrome” for microorganism culturing and to assess biofilm formation, on the other hand the co-culture products of a macrophage cell line RAW264.7 and Candida albicans and the effect of tumor necrosis factor-α (TNF-α) were evaluated for their impact on the proliferation and biofilm-forming abilities of different bacterial strains. Results Compared to a control group, the treatment group exhibited significant changes in gut microbiota, including increased biofilm formation, which was mitigated by Huoxiang Zhengqi Water. In the model group, fungal translocation was observed, potentially triggering an inflammatory response. Intraperitoneal injections of various bacterial strains in mice reproduced the sticky stool characteristics. Both mice and human subjects with “Dampness Syndrome” displayed elevated serum levels of inflammatory cytokines TNF-α and interleukin-17 A (IL-17A). Interestingly, Saliva samples from individuals with “Dampness Syndrome” showed elevated TNF-α levels, accompanied by thick and greasy tongue fur. Culturing samples from the tongue coating of individuals in the “Dampness Syndrome” group revealed an increased biofilm formation capability. C. albicans co-cultured with RAW264.7 cells increased TNF-α secretion, and the supernatant promoted pathogenic bacterial proliferation and biofilm formation. TNF-α specifically enhanced biofilm formation in microorganism like C. albicans and Staphylococcus aureus, with minimal effect on beneficial bacteria like Lacticaseibacillus paracasei and Lactiplantibacillus plantarum in the tested conditions. Conclusions These findings provided new insights into the biological mechanisms of ‘Dampness Syndrome’ and support the therapeutic role of Huoxiang Zhengqi Water in treating symptoms associated with microbial dysbiosis and inflammation. Additionally, they indicate that TNF-α seems to have selective effects in promoting the proliferation and biofilm formation of different microbial species.